Diagnosis and Treatment of Postoperative Myocardial Infarction: A Retrospective Cohort Study on 600 Cardiac Surgery Patients - Saimir Kuci; Marsela Goga; Alfred Ibrahimi; Ervin Bejko; Stavri Llazo; Jonela Burimi; Esmerilda Bulku; Andi Kacani; Ermal Likaj; Ali Refatllari; Selman Dumani; Klodian Krakulli; et al. (Albanian Journal of Trauma and Emergency Surgery)
Introduction: Postoperative myocardial infarction (PMI) is a severe complication after cardiac surgery, significantly impacting patient outcomes. Acute PMI after cardiac surgery is an infrequent event that can evolve rapidly and become a potentially life-threatening complication. Multiple factors are associated with acute PMI after cardiac surgery and may vary by the type of surgical procedure performed. Although the criteria defining nonprocedural myocardial ischemia are well established, there are no universally accepted criteria for diagnosing acute PMI. This retrospective study analyzed 600 patients who underwent cardiac surgery at a single center over one year. The incidence, diagnosis, and management of PMI were evaluated, focusing on diagnostic methods, therapeutic interventions, and the role of intra-aortic balloon pumps (IABPs). Our findings provide insights into the anesthesiologist’s role in identifying and managing PMI, highlighting strategies to reduce morbidity and mortality in this high-risk population.